Tolerance to phenanthrene by fungi isolated from an ecological reserve of Mato Grosso, Brazil (Research, Society and Development, 2021)
The selection of species with potential to degrade Polycyclic Aromatic Hydrocarbons (PAHs) is a fundamental step for the success of bioremediation programs. Among some methods, the contaminant tolerance test of interest has helped researchers to obtain organisms with the potential to degrade PAHs. Thus, the objective of this work was to analyze the potential of fungi, isolated from an ecological reserve in the Brazilian Midwest, to tolerate phenanthrene, a high toxicity HPA found in petroleum and its derivatives. For this purpose, fungus culture discs (8mm), obtained after 7 days of growth in MEA 2%, were transferred to Petri dishes containing MEA 0.2%, after superficial inoculation with phenanthrene crystals and incubated at 28 °C. Mycelial growth was measured for a period of 10 days in the absence and presence of different concentrations of phenanthrene (200 µg/mL, 600 µg/mL and 1000 µg/mL), in triplicate. Data were analyzed using fungal growth rate (FC), fungal growth inhibition (FCI) and analysis of variance (ANOVA) followed by Tukey's test (p>0.05). On the tenth day of growth, Phanerochaete australis SA18, Disporotrichum dimorphosporum SA09 and Lentinus crinitus SA37 stood out, with the highest CF and low ICF, consequently. P. australis tolerated all different concentrations of phenanthrene and stood out statistically from the other fungi. From these results, further studies with P. australis are suggested, on enzyme production, degradation capacity and production of phenanthrene metabolites.